Revision of the family Carabodidae (Acari: Oribatida) V (Fifth part). Redescription of Congocepheus latilamellatus Mahunka 1984, with complementary studies of C. ornatus, Mahunka 1983. Descriptions of Tanzaniacepheus gen. nov. and Zimbabwecepheus gen. nov. - Fernandez, Nestor; Leiva, Sergio; Jordaan, Anine (Zootaxa, 2017)
Redescription of Congocepheus latilamellatus, with complementary studies of Congocepheus ornatus. Congocepheus latilamellatus is a senior synonym of C. ornatus. Two new genera, Tanzaniacepheus and Zimbabwecepheus are described with type species Tanzaniacepheus ornatus n. comb. and Zimbabwecepheus maidii gen. nov., sp. nov.